Peningkatan Kapasitas Usaha Melalui Digitalisasi dan Legalitas Usaha pada Usaha Rumah Panrita Kabupaten Barru: Enhancing Business Capacity through Digitalization and Business Legality in Rumah Panrita, Barru Regency - Rahim, Abd; Syawal, Syawal; Damis, Sariana; Diana, Diana; Wisarna, Wisarna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Amidst the challenges of competitiveness and the demands of the digital era, MSMEs (Micro, Small, and Medium Enterprises) require strategic interventions to grow. This can involve engaging various parties to help enhance a business's capacity. Academics play a crucial role as a bridge to increase knowledge and facilitate these efforts through community service. This community engagement program aims to strengthen the capacity of the "Rumah Panrita" MSME, which operates in the coffee sector in Barru Regency. The method employed was participatory training covering four main pillars: (1) product diversification, (2) digital marketing strategy, (3) the importance of business legality, and (4) practical coffee brewing training. Impact evaluation was conducted using a mixed-methods approach. Quantitative analysis utilized a paired samples t-test on participants' pre-test and post-test results. The study revealed comprehensive success. Quantitatively, there was a statistically significant increase (p < 0.05) in participants' knowledge scores, with the average score rising from 13.13 to 13.87. This result was strongly supported by qualitative analysis through participatory observation, which indicated high levels of enthusiasm, active discussion, and initiative among participants. A shift in mindset and strong internal motivation to adopt new knowledge became tangible evidence of the MSME's readiness to transform. This activity concludes that the empowerment program was successful, evidenced by the convergence of significant statistical data and rich qualitative observations, which collectively demonstrate a positive impact and the readiness of "Rumah Panrita" UMKM for business transformation.